2017
DOI: 10.1016/j.jsams.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The provision of medical care in English professional football: An update

Abstract: Objectives To compare the current methods of appointment, qualifications and occupational experience of club doctors and physiotherapists in English professional football with (i) those outlined in a study published in 1999, and (ii) Football Association (FA) medical regulations. Design Qualitative. Methods Postal questionnaire survey of (head) doctors and physiotherapists at each of the clubs in the English Premiership, Championship and Football Leagues 1 and 2. Response rates of 35.8% and 45.6% respectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…None of the medical staff in our sample had ever been asked about their qualifications or professional registration when being hired, nor were any of them formally interviewed. Rather, for all of the medical professionals in our study, personal recommendations shared within the combat sport community secured employment, reminiscent of informal hiring practices seen in other studies 11,12 .…”
Section: Resultsmentioning
confidence: 81%
“…None of the medical staff in our sample had ever been asked about their qualifications or professional registration when being hired, nor were any of them formally interviewed. Rather, for all of the medical professionals in our study, personal recommendations shared within the combat sport community secured employment, reminiscent of informal hiring practices seen in other studies 11,12 .…”
Section: Resultsmentioning
confidence: 81%
“…He added ‘With the advent of the Premier League and … when the EPPP [Elite Player Performance Plan, introduced in 2011] was introduced with category one status with the academy, that meant recruiting a lot of staff and they weren’t aware of any of these principles so it’s been hard work policing that side of it’. These comments reflect both the tendency of Premiership clubs to have larger MSSTs (Malcolm et al, 2017), and the traditional hierarchy of healthcare professions in which doctors normally oversee the work of other healthcare workers.…”
Section: Resultsmentioning
confidence: 99%
“…Their primary identities as medical professionals, as well as their ability to resist pressures from managers to deviate from good practice, are likely to be reinforced by their everyday work setting (Freidson, 1970), which typically differs from the work setting of club physiotherapists. Of particular relevance in this regard is the fact that, unlike most physiotherapists, almost all of whom are full-time employees of the club, most doctors are only employed on a part-time basis (Malcolm et al, 2017). Thus most doctors spend most of their working time in, and almost certainly derive most of their income from, medical practice outside the football club.…”
Section: Resultsmentioning
confidence: 99%
“…This raises the question as to whether the participants fully understand what 'suitably covered' means. Indeed, research has found that appointments of medical staff in the Football Association (FA) and MMA are still informal and that continuous professional development (CPD) requirements are not prioritised despite the current medical regulations [25][26][27]. There is, therefore, reason to believe that across sports, there is either practice of ignorance or disregard for the regulations.…”
Section: Medical Personnel/provisionmentioning
confidence: 99%